Family Histories of Mental Illness and Violence in State Patients - Vogts, Elizabeth (Department of Psychiatry and Mental Health, 2022)
Background: It is known that both severe mental illness and violence have genetic components. Multiple genes play a role in the cause of violent behaviour. Violence is one of the leading causes of death for young people in South Africa and yet little is known about its prevalence in state patients and their family members. Aim: This study aimed to investigate the prevalence of violence and mental illness in the families of state patients, to what extend these coincide and to compare schizophrenia and mood psychosis in that context. Setting: The study included 60 state patients' folders, all of whom were diagnosed with a psychotic disorder, in accordance with DSM5 criteria. The subjects were divided into two groups: those who have committed violence and those who have not committed violence. Method: Patients' folders were selected by purposive sampling. These folders were then reviewed by the researcher and a questionnaire was completed. Results: Violent patients had more first-generation relatives with violent convictions (68.2%), compared to 36.4% of non-violent patients. Only 3.3% of non-violent patients witnessed domestic violence, whereas 13.3% of violent patients witnessed domestic violence. A significantly higher proportion of patients with bipolar disorder had been convicted of physical assault (p=0.035). 17.6% of violent schizophrenia patients had a family history of violence and mental illness, compared to 18.2% of violent patients with mood psychoses which is not statistically significant. Conclusion: It was found that violence runs in families and that mental illness and violence was prevalent in the described group. Of further concern was that more violent patients witnessed domestic violence compared to non-violent patients, emphasising the idea that the cause of violence is multifactorial (genetic, environmental), and that identification of not only high-risk patients but also high-risk families need to be implemented.